TRANSFORMATION OF PUBLIC POLICY IN THE FIELD OF EDUCATION OF NURSES ON QUESTIONS OF HELP AT THE END OF LIFE IN THE CONTEXT OF UN SUSTAINABLE DEVELOPMENT GOALS AND DEMOCRATIZATION IN UKRAINE - Вольф, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
Possible directions of transformation of the state policy in the field of education of nurses in a narrow issue of end-of-life nursing care in the context of the UN Sustainable Development Goals are identified. The 70th UN General Assembly where civic society organizations actively participated adopted the 2030 Agenda for Sustainable Development as part of the Summit on Sustainable Development in September 2015, which included 17 Global Sustainable Development Goals. Global Goal 4.7 stated: «By 2030 ensure all learners acquire knowledge and skills needed to promote sustainable development, including among others through education for sustainable development and sustainable lifestyles, human rights, gender equality, promotion of a culture of peace and non-violence, global citizenship, and appreciation of cultural diversity and of culture’s contribution to sustainable development». This Goal also applies to medical education (in particular, for nurses). The improvement of the content of this education is actual in the context of the implementation of medical reform in Ukraine.A content analysis of the international curriculum for nurses and its comparison with teaching documents implemented in medical colleges in Ukraine has been made. The program developed in the United States with active participation of civil society organisations has been found to be consistent with UN Sustainable Development Goal 4.7. Comparing these documents, we can easily see Ukrainian curricula inconsistency with both international standards of nursing training and the UN Sustainable Development Goals. These curricula form only a generalized understanding of the value of cultural diversity and human rights and do not include issues of social justice, inclusion, multidisciplinary cooperation etc.A content analysis of the Strategy for the Development of Medical Education in Ukraine, approved by the Order of the Cabinet of Ministers of Ukraine of 27th February, 2019, № 95-r, revealed that the document does not provide for the inclusion of aspects set out in Global Goal 4.7.Participation of citizens in development of national educational policy is the obligatory precondition for forming of the democratic society and encourages better compliance of educational programs with the needs of the population.   It is argued that in the context of medical reform, it is necessary to change the approach to the content of medical education and the formation of the competence of nurses, in particular, in the field of end-of-life care in undergraduate education. Cross-sectoral and multidisciplinary cooperation is needed to develop quality training programs for nurses in line with international standards; this could be done in particular by involving civil society institutions in the process.